Analysis of spatial vibrations of piezoceramic eccentric cylindrical shells interacting with an annular fluid layer - Sergei Lekomtsev; Sergey Bochkarev; Alexander Senin (Fracture and Structural Integrity)
The work is devoted to a numerical study of the behavior of vertically oriented eccentric (non-coaxial) electroelastic shells, containing a fluid in the gap between them. The solution of the problem is found in the framework of a three-dimensional formulation using the finite element method. The shells are made of the piezoelectric material polarized in the radial direction. Thin-walled structures are considered in the framework of the classical theory based on the Kirchhoff – Love hypotheses, as well as the equations of linear electroelasticity. The distribution of the electric potential through the thickness is assumed linear. The fluid is considered within the framework of a potential theory. The study of the low natural frequencies and vibration modes is carried out for different variants of the boundary conditions at the edges of the shells, the level of fluid in the gap and the eccentricity of the inner shell. The influence of the electric boundary conditions specified on the parts of the shells surfaces covered with electrodes is estimated.